Strategi Pemberdayaan Budaya Minat Baca Santri TPQ Dalam Meningkatkan Literasi - Nazilah, Muslikhatun; Darmaningrum, Khaerunnisa Tri (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
This research discusses the cultural empowerment of students' interest in reading at the Al Ikhlas Qur'an Education Park, Petarukan, Pemalang. Developing an interest in reading is important because reading is the main thing for children to gain knowledge and experience. The method used in this research is a qualitative descriptive method. The results of this activity show why students are less interested in reading. Santri are always lazy, think reading is a boring activity, and many do not understand the importance of reading books. Efforts made are to understand the importance of reading, namely by using the storytelling method to increase children's literacy and holding reading events together and freeing students to choose the books they want.